Biologia so camarão Pleoticus muelleri (Bate, 1888) (Crustacea: Decapoda: Penaeoidea) em seu limite norte de distribuição no Atlântico Sul, numa região sobre o efeito da ressurgência oceânica - Sancinetti, Gustavo Sérgio [UNESP] (2015)
This study evaluated the effect of environmental factors on the spatial and temporal distribution of P. muelleri shrimp in an area of influence of the resurgence of Cabo Frio. Samples were collected monthly, during two years, on the coast of Macae, State of Rio de Janeiro (22 47 S, 41 45 W), between 5 to 45 meters of depths. Environmental parameters temperature and salinity of the water, as well as texture and content of organic matter in the sediment ware analyzed. A total of 14236 individuals of P. muelleri were captured. The highest abundances occurred mainly in the 25 and 35 meters deep and spring II. Environmental factors with significant relationship in the abundance of shrimp were the temperature and salinity. These results indicate that particularly when the temperature is below 18° C, there is a greater abundance of P. muelleri, remaining in the deeper areas even when temperatures appear to be most favorable in the shallow region (T <22° C). The preference for deeper areas indicates that there is not migration to internal areas. P. muelleri appears to prefer salinities above the deepest region 32. The presence of individuals during the two year study indicates that there is an established population in the region, which is influenced by the resurgence of Cabo Frio